Evaluating time-dependent and bond characteristics of a lightweight concrete mix for Kansas prestressed concrete bridges - Holste, Joseph Robert (Kansas State University, 2010)
This thesis details findings from testing done to determine bond and time-dependent characteristics of two lightweight concrete mixes. The lightweight mixes were tested to possibly provide a more cost-effective solution to replacing some of Kansas’ older bridges. Testing included use of a conventional lightweight mix and a self-consolidating lightweight mix. Sixteen Inverted T-beams were cast at a prestress plant to determine prestress losses that had occurred in the two lightweight mixes. These losses were compared to ACI, PCI, and AASHTO code equations. Creep and shrinkage prisms were also cast and measured to accurately determine creep and shrinkage variables for the two lightweight mixes. Twelve flexural beams were also cast at the prestress plant and tested at Kansas State University’s Civil Engineering Structures Laboratory to experimentally test development lengths of the lightweight mixes and to compare results with ACI code equations. This study found compressive strengths of the lightweight concrete mixes varied greatly from laboratory testing. Low concrete strengths caused the prestress losses to be greater than the predicted code values. Flexure beam testing showed several of the beams were subject to strand slip, causing a sudden violent failure.
Keywords: lightweight; concrete; prestressed; SCC; Engineering, Civil (0543)